An Efficient Itinerary Management Scheme for Electric Vehicles using ACO - Hooda, Deepika (My University, 2016)
Electric grid has been transformed to smart grid by incorporating ICT infrastructure. This transformation of a smart grid fromm a conventional grid is necessary to achieve environmental targets. Smart grid technology has significantly changed the way of generation and distribution of electricity which not only helps to decrease the demand of power and cost savings, but also can comparably improve the reliability and efficiency of power system. An electric vehicle, a component of smart grid is the vehicle which uses electric motors for moving the vehicle. Itinerary planning of EV is to manage the whole journey without exhausting battery charging. To find the best route in terms of power consumption of EVs, itineray is planned. Keeping this in mind, we proposed an algorithm which uses ant colony optimization technique to generate the optimized route for electric vehicle to reach its destination from a specific source.
Keywords: Smart grid; electric vehicles; route optimization; Ant colony optimization